Landscape, belonging & identity in North-west Zimbabwe: a semiotic analysis - Matanzima, Joshua; Saidi, Umali (Routledge, 2021)
Research has shown that there is an inextricable relationship between landscape, belonging and identity. Landscapes possess marked capacities of triggering acts of self-reflection, inspiring thoughts about who one presently is; memories of who one used to be or musings of who one might become. Using semiotics, the paper explores ethnic names, Basilwizi (BaTonga) and Goba (Shangwe) showing how these denote aspects of belonging and identity. These ethnic labels, Basilwizi and Goba, signify BaTonga and Shangwe cultural and historical connections to the Zambezi Valley in Zimbabwe. Thus, the paper reveals that the BaTonga and Shangwe continue to negotiate for space as well as to characterise the ‘politics’ of what ‘landscape’ means. This provides one with knowledge of appreciating subtle historical and cultural factors attached to land reforms in general. Researchers used oral interviews and extensive document analysis as data gathering tools for the study.